Assessment of Efficiency of Innovation Projects Financing through the Exit Strategies of Venture Capital Investors - AKHMEJANOVA, Tatiana Alexandrovna; VIKULINA, Valeria Vladimirovna; VOTCHEL, Lilia Midykhatovna; IVASHINA, Natalya Stanislavovna; KUZNETSOVA, Margarita Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The essence of venture (risk) business consists in providing financial resources to innovative companies, which have no other sources of funding. Venture capital investor invests money capital in exchange for a share in the company. Peculiarity of venture capital investors is that when investing funds in any investment project, they expect at the same time to exit out of it in a few years through a most preferred manner. The article evaluates alternative exit strategies of investors from venture capital, which can be classified as both desirable and undesirable (negative). In this article all options of the exit strategies are ranked according to descending order of their attractiveness: from IPO (Initial Public Offering) to write-offs. As a result of the conducted analysis of the venture and direct investment market in the Russian Federation for the period of 2006-2014 it has been identified that the most frequently used exit is that of selling own shares to a strategic investor. Statistics has demonstrated that the most effective exit through IPO was used by investors not too extensively. However, relatively small number of write-offs was noted that is a positive feature of the Russian market of venture capital. In the future, such options as IPO and the buy-back will have the greatest prospects.